2009
DOI: 10.1155/2009/159767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Level on Oral Health in Peritoneal and Hemodialysis Patients

Abstract: Background. In previous studies, the oral and dental health statuses were compared in hemodialysis (HD) and peritoneal dialysis (PD) patients without taking into account the effect of educational levels on oral health. Hence we aimed to make a comparison of these parameters based upon the subjects educational levels. Patients and Methods. 76 PD (33 males, 43 females-mean age: 44 ± 12 years) and 100 HD (56 males, 44 females-mean age: 46 ± 14 years) patients were included. The number of decayed, missing and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
3
9
0
5
Order By: Relevance
“…Concerning gender the results show that there is no significant relationship among gender factor and patient's knowledge toward hemodialysis fatigue in both study and control group for pre and posttest This finding is agrees with study of Green et al, which states that there is non-significant relation between the gender (Prevalence and Demographic and Clinical Associations of Health Literacy in Patients on Maintenance Hemodialysis) (18) . This finding is supported by Bayraktar et al, there is no significant correlation between gender in his study (19) . This might be because the simplicity of construction of instructional program for both gender and the urgent need for education for caring them hemodialysis fatigue at table (5).…”
Section: Discussion Of Comparison Significant Of Patients' Knowledge supporting
confidence: 76%
See 1 more Smart Citation
“…Concerning gender the results show that there is no significant relationship among gender factor and patient's knowledge toward hemodialysis fatigue in both study and control group for pre and posttest This finding is agrees with study of Green et al, which states that there is non-significant relation between the gender (Prevalence and Demographic and Clinical Associations of Health Literacy in Patients on Maintenance Hemodialysis) (18) . This finding is supported by Bayraktar et al, there is no significant correlation between gender in his study (19) . This might be because the simplicity of construction of instructional program for both gender and the urgent need for education for caring them hemodialysis fatigue at table (5).…”
Section: Discussion Of Comparison Significant Of Patients' Knowledge supporting
confidence: 76%
“…This finding is supported by results obtained from study done by Bayraktar et. al., who stated that there is a significantly higher numbers (P < .001) and were detected with higher educational levels, whereas no significance was detected in the hemodialysis control group (19) . This result also comes in agreement with Ford et al , who reported that there is a significant relationship of the knowledge level of the experimental group were more (P < .05) After 6 months, improvements in knowledge were significantly show high in the intervention group, than in the control group (20) .…”
Section: Discussion Of Comparison Significant Of Patients' Knowledge mentioning
confidence: 93%
“…PD differs from HD as PD patients can continue dialysis at home. This finding supports the fact that PD groups pay more attention to oral hygiene to prevent calculus formation [13]. The higher amount of dental calculus in the HD group could also be related to the characteristics of their saliva itself and other manifestations of disturbed Ca/P homeostasis [1].…”
Section: Discussionsupporting
confidence: 70%
“…Several studies reported that patients undergoing PD therapy have a better quality of life and higher education levels. This could be because patients undergoing HD therapy have to spend approximately 4 h several times a week in dialysis centers, which often leads to post-HD fatigue [4,12,13]. Oral health negligence could be explained by the routine dependency on health centers and their main concern about other systemic difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that oral home care practices tended to be less frequent in CKD individuals who did not seek dental care on a regular basis [20,21]. It was shown in a study, that depending upon the educational level of the patients, that is, with higher educational levels, the number of filled teeth was higher patients, with no significant statistical difference.…”
Section: Discussionmentioning
confidence: 94%